Improving Efficiency of Evaporated Cu2ZnSnS4 Thin Film Solar Cells by a Thin Ag Intermediate Layer between Absorber and Back Contact - Hongtao Cui; Chang-Yeh Lee; Wei Li; Xiaolei Liu; Xiaoming Wen; Xiaojing Hao (International Journal of Photoenergy)
A 20 nm Ag coating on Mo back contact was adopted to improve the back contact of evaporated Cu2ZnSnS4 (CZTS) solar cells. The Ag layer helped reduce the thickness of MoS2 which improves fill factor (FF) significantly; additionally, it reduced secondary phases ZnS and SnS2−x, which may help carrier transport; it was also involved in the doping of the absorber layer, which compensated the intrinsic p-type doping and therefore drags down the doping level. The doping involvement may enlarge the depletion region and improve lifetime of the absorber, which led to enhancing open circuit voltage (VOC), short circuit current density (JSC), and efficiency significantly. However, it degrades the crystallinity of the material slightly.